PENINGKATAN KEMAMPUAN SENI DALAM PEMBELAJARAN MELUKIS DENGAN TEKNIK USAP ABUR ANAK KELOMPOK B - KUSMIATI KUSMIATI (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
The research I did was motivated by the artistic ability of group B children who were still not well developed, of the 15 children who had developed only 5 children. This is a problem for the teacher. This problem needs to be solved immediately, the solution is through painting activities with the Blurry Wipe technique. The purpose of this study is to describe the application of painting and to describe the improvement in the development of art in group B children at the Kepanjenkidul I Kindergarten in Blitar City. The lack or low level of Children's Art in terms of painting with the Blurry Wipe technique in group B at the Kepanjenkidul I Kindergarten in Blitar City. This study used classroom action research which was carried out in 2 cycles, each cycle consisting of 2 meetings. Each cycle consists of planning, action, observation and reflection. The application of painting can improve the ability of art seen from the first cycle of the first meeting the teacher's activity got 61.5% and the children's activity was 53.8%, the child's cleanliness score was 33.3%, the child's accuracy value was 40.0%, the child's beauty value was 46.6 %, the value of children's creativity 53.3% was improved at meeting 2. Meeting 2 Teacher's activities obtained 69.2%, children's activities were 69.2%, children's hygiene scores were 40.0%, children's accuracy scores were 33.3%, children's beauty scores 33.3%, the value of children's creativity is 60.0% because it has not yet reached completeness, so it is corrected in the second cycle. The results of the second cycle of the first meeting of the teacher's activity obtained 79.9%. Children's activity was 69.2%, the value of children's cleanliness was 60.0%, the value of accuracy was 66.6%, the value of children's beauty was 73.3%, the value of children's creativity was 80.0%. Meeting 2 Teacher activity 100%, child activity 92.3%, child hygiene score 80.0%, accuracy value 86.6%, beauty value 93.3%, child creativity value 93.3%. ABSTRAKPenelitian yang saya lakukan ini dilatarbelakangi oleh kemampuan seni anak kelompok B masih belum berkembang secara baikdari 15 anak yang sudah berkembang hanya 5 anak saja. Hal ini merupakan masalah bagi guru.Permasalahan ini perlu segera ada pemecahanya,solosi pemecahanya yaitu melalui kegiatan Melukis dengan teknik Usap Abur. Tujuan Penelitian ini mendiskrisikan penerapan Melukis dan mendiskripsikan peningkatan perkembangan Seni pada anak kelompok B TK Negeri Kepanjenkidul I Kota Blitar. Minimnya atau rendahnya Seni Anak dalam hal melukis dengan tehnik Usap abur pada kelompok B di TK Negeri Kepanjenkidul I Kota Blitar. Penelitian ini menggunakan penelitian tindakan kelas yang dilaksanakan 2 siklus, masing-masing siklus terdiri 2 pertemuan. Setiap siklus terdiri dari perencanaan,tindakan,observasi dan refleksi. Penerapan Melukis dapat meningkatkan kemampuan Seni terlihat dari pada siklus I pertemuan pertama Aktivitas Guru memperoleh 61,5% dan Aktivitas Anak 53,8%,nilai kebersihan anak 33,3%,nilai ketepatan anak 40,0%,nilai keindahan anak 46,6%,nilai kreativitas anak 53,3% diperbaiki pada pertemuan 2. Pertemuan 2 Aktivitas Guru memperoleh 69,2%,Aktivitas anak 69,2%,nilai kebersihan anak 40,0%, nilai ketepatan anak 33,3%,nilai keindahan anak 33,3%, nilai kreativitas anak 60,0% karena belum mencapai ketuntasan maka diperbaiki pada siklus II. Hasil siklus II pertemuan pertama Aktivitas guru memperoleh 79,9% Aktivitas anak 69,2%,nilai kebersihan anak 60,0%,nilai ketepatan anak 66,6%,nilai keindahan anak 73,3%,nilai kreativitas anak 80.0%. Pertemuan 2 Aktivitas guru 100%,Aktivitas anak 92,3%,nilai kebersihan anak 80,0%,nilai ketepatan 86,6%,nilai keindahan 93,3%,nilai kreativitas anak 93,3%.